New equivalence relation for the classification of fuzzy subgroups of symmetric S4 (2018)
In this paper a new equivalence relation for classifying the fuzzy subgroups of finite groups is studied. Without any equivalence relation on fuzzy subgroups of group G, the number of fuzzy subgroups is infinite, even for the trivial group. The number of distinct fuzzy subgroups with respect to the new equivalence relation is obtained for S4.